(untitled) (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
Elderly people experience a decrease in their body’s flexibility due to a lack of activities such as gymnastics, which can lead to decreased flexibility. The purpose of this study was to determine the level of flexibility of the elderly in the healthy heart gymnastics community at the Sidoarjo Youth, Sports, and Tourism Office. The sample in this study was 25 elderly people using total sampling. This study used a quantitative descriptive method. Using a chair sit and reach test to measure the flexibility of the elderly. The results showed that 25 elderly people were aged 60-79 years on average, and the results of the chair sit and reach test showed an average of 6.49 ± 4.22. This study concluded that most of the elderly’s abilities were elderly, with a total of 19 elderly people having a normal level of flexibility and 6 elderly people having less flexibility.